Model of Causal Factors Affecting Management Effectiveness Savings for Production in Buriram - Panyayong, Wisanu (Journal of Local Governance and Innovation, 2019)
There are three aspects in this study. The first aspect is to design and develops the causal factors model influencing performance of the management of savings groups for production. The second aspect is to study the causal factors model influencing performance of the management of savings groups for production. The last aspect is to confirm the causal factors influencing performance of the management of savings groups for production in Buriram province. This study is both qualitative and quantitative research. The sample of the study is the management of savings groups for production committee that involved 450 people. The research instruments are questionnaire and interview. The data analysis are percentage, the samples mean, standard deviation, skewness, kurtosis, median value for median range between quartiles and confirm from professor and analysis data by structural equation modeling (SEM). The result of the study found that there are four variables in causal factors model influencing performance of the management of savings groups for production. There are participation, group’s learning, leader characteristic and working transparency. The causal factors model influencing performance of the management of savings groups for production consistent with empirical data, chi-square (X2) =157.04. significance =.05, p-value = 0.95400 ,(X2/df) = 1.42 , (GFI)= 0.69 ,(AGFI) = 0.86 ,(RMSEA) = 0.140. The highest total influence of casual factor is leader characteristic. The result of confirm from the professors found that they have consistent comments with causal factors model influencing the performance of the management of savings groups for production in Buriram province.